Long-term effects of early childhood care and education - Christopher Ruhm; Jane Waldfogel (Institute for the Study of Labor (IZA), 2011)
This paper critically reviews what we know about the long-term effects of parental leave and early childhood education programs. We find only limited evidence that expansions of parental leave durations improved long-run educational or labor market outcomes of the children whose parents were affected by them, perhaps because benefits are hard to measure or confined to sub-groups, or because leave entitlements were sufficiently long, even before recent extensions, to yield most potential benefits. By contrast, expansions of early education generally yield benefits at school entry, adolescence, and for adults, particularly for disadvantaged children; however the gains may be less pronounced when high quality subsidized child care was available prior to the program expansion or when subsidies increased the use of low quality care.
urn:nbn:de:101:1-2012010913691
Keywords: J13; J18; J48; 330; parental leave; early childhood care and education; Kinder; Kinderbetreuung; Frühkindliche Bildung; Wirkungsanalyse; Bildungsniveau; Welt